KONFIRMASI SPESIFITAS GAD65 TERHADAP ANTI-GAD65 PADA TIKUS DM DAN PASIEN DM TIPE 1 - Aulanni’am Aulanni’am; Djoko Wahono Soeatmadji; Sutiman B Sumitro (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2006)
The use of glutamic acid decarboxylase (GAD65) from bovine brain has been studied to obtain basic knowledge and diagnosis and prediction of Type 1 Diabetes Mellitus (DM) patients. The importance of GAD65 in DM diagnosis based on its patogenesis. One of the autoimmune marker that can be used to detect beta-pancreas destruction in Diabetes Type I is the antibody to glutamic acid decarboxylase (GAD65). Most of the pre-diabetic patients indicate the reactive autoantibody to GAD65. For early detection of anti-GAD65 in the serum of the patient, human recombinat GAD65 has been succeed to be used. However this is not economical, therefore, it is necessary to find the alternative source of cheaper GAD65. The aim of this research is to develop an early detection kit of Type 1 DM based on antibody-GAD65, since the longest patient suffering from DM has higher probability to be complicated, especially for uncured patients. The anti- GAD65 antibodies induced by anti-GAD65 synthetized and labelled by alkaline phosphatase can be used as reagent detection early DM patients. The ten patients of DM as samples (positive of anti-GAD65) and five rats of DM were positive with western blott technique using reagents as result of this research. It can be concluded, GAD65 enzyme isolated from bovine brain induced anti-GAD65 production and have possibilities to be packaged in a diagnostic kit for patient pre DM.